2021
DOI: 10.3390/cancers13092148
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of KRAS Mutational Status between Primary Tumors and Liver Metastases in Colorectal Cancer: Impact on Long-Term Survival Following Radical Resection

Abstract: If KRAS mutation status of primary colorectal tumor is representative of corresponding colorectal liver metastases (CRLM) mutational pattern, is controversial. Several studies have reported different rates of KRAS discordance, ranging from 4 to 32%. Aim of this study is to assess the incidence of discordance and its impact on overall survival (OS) in a homogenous group of patients. KRAS mutation status was evaluated in 107 patients resected for both primary colorectal tumor and corresponding CRLM at the same i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…As a result, 48 mRNAs were chosen to construct a prognostic model ( Table 2 ). The risk score = (Coef1 * expression level of mRNA1) + (Coef2 * expression level of mRNA2) + (Coef n * expression level of mRNA n), mRNA coefs were calculated from multivariate cox regression coefficients [20] . The independent forecast value of the prognostic risk model was evaluated by univariate cox regression analyses, the result indicated that risk score, age and grade had significant values ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, 48 mRNAs were chosen to construct a prognostic model ( Table 2 ). The risk score = (Coef1 * expression level of mRNA1) + (Coef2 * expression level of mRNA2) + (Coef n * expression level of mRNA n), mRNA coefs were calculated from multivariate cox regression coefficients [20] . The independent forecast value of the prognostic risk model was evaluated by univariate cox regression analyses, the result indicated that risk score, age and grade had significant values ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between overall survival (OS) and mRNA expression was identified using the univariate cox regression analysis with a criterion of p-value < 0.001. Multivariate cox regression analysis (stepwise regression method, p-value < 0.2) was used to determine the independent factors for prognosis prediction [20] . Founded on the results of multivariate cox regression, we established a prognostic model, and patients were divided into a low or a high-risk group according to the median level of risk scores.…”
Section: Methodsmentioning
confidence: 99%
“…As previously reported [ 17 , 18 , 19 , 20 ], KRAS mutation analysis was performed at the Anatomic Pathology Unit of our University Hospital. Tumoral tissue was identified in hematoxylin-and-eosin-stained sections of formalin-fixed, paraffin-embedded archival blocks.…”
Section: Methodsmentioning
confidence: 99%
“…All KRAS mutations found were pathogenic mutations. As previously described [ 17 , 18 , 19 , 20 ], KRAS codons 12, 13, 59, 61, 117 and 146 were amplified in one PCR. Thermal cycling conditions were: 95 °C for 12 min followed by 40 cycles of 95 °C for 10 s, 55 °C for 20 s and 72 °C for 20 s. PCR conditions were as follows: primer concentration 200 nmol L −1 , MgCl 2 concentration 2 mmol L−1; 30 ng of genomic DNA and 12.5 µL of Eppendorf Prime mastermix (Eppendorf, Milan, Italy) in a final reaction volume of 25 µL.…”
Section: Methodsmentioning
confidence: 99%
“…Studies reported discordances ranging from 4 to 32% to 100% concordance [48][49][50][51][52][53][54][55]. An Italian team managed by Ardito analyzed KRAS status for both the primary tumor and completely resected liver metastases in 107 patients and found a discordance incidence of 15.9% [56]. The main characteristics of these studies are presented in table II below.…”
Section: Impact Of Kras Mutation On the Treatment In The Metastatic S...mentioning
confidence: 99%